A delay resilient approach in cyber physical systems for Industrial IoT - Rawal, Akshay (Nanyang Technological University, 2019)
Current paradigm shifts in the ICT domain in particular, mobile, social, cloud and big data are urging computer networks for high bandwidth, ubiquitous accessibility, and dynamic management. OpenFlow network protocol helps in that goal as part of a Software-Defined Networking (SDN) movement to manage the connectivity of the multitude of devices in a network such as an Internet of things (IOT) network by differentiating between the control plane and data plane of the network and providing the bridge for interaction between the two planes. Industrial IOT is a special case of a cyber-physical system (CPS) that has strict time-based delay requirements for important tasks such as execution and monitoring of industrial systems. Network delay is an important design and performance characteristic of a computer network. Especially so in the case of Industrial IOT. However, the time-sensitive nature of Industrial IOT leads to traditional methods of measuring delay, such as flooding the network with as Internet Control Message Protocol (ICMP) packets, a critical failure in one of the fundamental requirements for the need of constant uptime of Industrial IOT. Therefore the need for measuring delay using novel approaches while conforming to the design of the OpenFlow protocol is important for Industrial IOT. In this paper, we present a previously explored idea for exploiting Link Layer Discovery Protocol (LLDP) packets for storing time information and further that approach by using a systematic method of ensuring end-to-end delay by dividing the delay into several parts and measuring each separately. We also exploit the Type-Length-Value field of LLDP packets to store a timestamp value to provide more accurate results. We also recommend a modification to the standard for Link-Layer Discovery Protocol especially for OpenFlow networks that requires the network applications to include the ability to easily add user-defined fields and update values using a managed application programming interface by default not only to help in overcoming the shortfall of a reliable delay measurement protocol but also provide a network-wide status information for networks that rely on OpenFlow.